RANCANG BANGUN SMART GENERATOR SET BERBASIS INTERNET OF THINGS MENGGUNAKAN APLIKASI BLYNK - Ricardo Martua Pasaribu; Muhammad Diono (Politeknik Caltex Riau, 2021)
At this time, the system for replacing electric power when it goes out using a generator set still uses a manual power replacement system, turning on the Generator Set and monitoring the Generator set manually by using human control. The use of human control is not practical nowadays, because the owner of the house or building when the electricity goes out must turn on the Generator Set and transfer the power manually, which in this process requires a very long time and excessive energy. The main objective of this research is to create a sophisticated Generator Set system with the help of IOT, which will later be named Smart Generator Set. Smart Generator Set features automatic power supply change, automatic generator set turn on and Generator Set monitoring via Android Application. To implement this feature, the Smart Generator Set works using the principle of Automatic Transfer Switch and Automatic Main Failure with the help of the NodeMCU microcontroller. Testing the transfer of the power supply from PLN to the Generator Set or from the Generator Set to PLN is said to be almost perfect, with a very fast rate of power transfer. In several tests, the resulting displacement time lag is always under 10 seconds. Sensor testing for monitoring Generator Sets has a very good level of precision. Where in several samples of testing each sensor obtained a level of accuracy and precision above 95%.